Does a degree in medicine or a specialist programme or socioeconomic status advance the career of general practitioners in primary healthcare? - Zheng, Dandan; Alam, Gazi Mahabubul; Bashir, Karima; Hassan, Norlizah Che; Lei, Miao (Public Library of Science, 2026)
Extensive studies have investigated possible mechanism to improve the career path of general practitioners (GPs) in order to ensure the primary healthcare system (PHC) functions properly. Nevertheless, this problem persists in many countries and it is aggravated by preferential policy. Against this background, the current study examined whether the diverse groups of GPs employed by the PHC system help to develop a sustainable PHC system or create a dysfunctional one. This quantitative cross-sectional survey sampled 12,767 graduates from 13 medical schools in China. Secondary data was collected on socioeconomic status (SES), career advancement, educational qualification, demographic characteristics and graduates’ employment information. The collected data was analyzed using group regression and mediation analysis. Results indicated that, among the 1,769 clinical physicians working in PHC institutions, the ratio of specialist to specialists transferred general practitioners and full general practitioners is 3:2:1, indicating a horizontal mismatch. Furthermore, medical graduates’ degree program type significantly relates to their career advancement and SES mediated the link between medical graduates’ degree program type and career advancement with an indirect effect: Internal Medicine SP-GP → SES → CA (β = 0.040, P < 0.001); Obstetrics and Gynecology SP-GP → SES → CA (β = 0.026, P < 0.001); Emergency Medicine SP-GP → SES → CA (β = 0.021, P < 0.001); Paediatrics SP-GP → SES → CA (β = 0.024, P < 0.001). This study contributes to discourse on SES and medical education by highlighting how medical education has evolved into a money-driven program in which students’ SES influences the program they select.